Kinematic parameters of jump shot in elite male basketball players - Stojanovic, E.; Radenkovic, M.; Bubanj, S.; Stankovic, R. (Facta Universitatis: Series Physical Education and Sport, 2019)
The primary aim of this study was to determine kinematic parameters of jump shot in elite male basketball players, by analyzing the release time for shooting, the angle of entry, and ball spin and. The secondary aim of this study was to examine possible differences in these kinematic parameters among the players associated with their playing position. Eighteen male basketball players (7 guards, 8 forwards, 3 centers) from six Serbian senior teams were tested. 94Fifty basketball sensor was used to obtain the following kinematic parameters of jump shot). The highest average measured values of shot release time were found in centres (1.23±0.23 s) and the lowest in guards (1.07±0.28 s), although these differences were not statistically significant. Further, centres had a lower angle of entry (36.6±2.08°) than guards (40.54±4.76°) and forwards (42.05±3.77°). The highest value of backspin was obtained by forwards (130±11.91 rotations / min). There were no significant differences between guards, forwards and centers in any kinematic variables (p>.01). The relationship between the body height and angle of entry was not significant (p>0.05). In conclusion, compared to centers, guards and forwards showed similar results for the examined variables. This evidence seems to support the theory that compared to guards and forwards centres have the weaker shooting techniques. Coaches should encourage all players, especially centers, to shoot from all positions.